2001
DOI: 10.1002/mrm.1202
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between human magnetostimulation thresholds in whole‐body and head/neck gradient coils

Abstract: Gradient coil magnetostimulation thresholds were measured in a group of 20 volunteers in both a whole-body gradient coil and a head/neck gradient coil. Both coils were operated using both x and y axes simultaneously (xy oblique mode). The waveform applied was a 64-lobe trapezoidal train with 1-ms flat-tops and varying rise times. Thresholds were based on the subjects' perception of stimulation, and painful sensations were not elic- The mean threshold curves were combined with the gradient system performance cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 16 publications
7
82
1
Order By: Relevance
“…[3] is transformed to: [7] or B Ն B min ϭ dB/dt͉ rheobase ⅐ t ch [8] Thus, the change in magnetic flux density ⌬B producing sensations at perception threshold should be a linear function of the pulse duration t according to Eq. [5].…”
Section: Theorymentioning
confidence: 99%
“…[3] is transformed to: [7] or B Ն B min ϭ dB/dt͉ rheobase ⅐ t ch [8] Thus, the change in magnetic flux density ⌬B producing sensations at perception threshold should be a linear function of the pulse duration t according to Eq. [5].…”
Section: Theorymentioning
confidence: 99%
“…Following the analysis of Stump and Pollack (14) (see Appendix A), who describe the evaluation of the magnetic field outside a spherical current distribution in the context of geomagnetism, it can be shown that the z-component of the magnetic field, B z (r, , ) inside a spherical surface (i.e., in the region where r Ͻ a) carrying a current distribution described by Eqs. [1] and [2] is given by…”
Section: Theorymentioning
confidence: 99%
“…Substitution into Eq. [2], followed by use of the relationship P n,1 ͑cos ͒ ϭ Ϫsin d͑P n ͑cos ͒͒ d , [9] shows that the required current distribution is of the form…”
Section: Spherical Axial Gradient Coilmentioning
confidence: 99%
See 2 more Smart Citations